Early onset muscarinic manifestations after wild mushroom ingestion. - Chew, Keng Sheng; Mohidin, Mohd Amin; Ahmad, Mohd Zikri; Tuan Kamauzaman, Tuan Hairul Nizam; Mohamad, Nasir (2008)
Despite being a favorite delicacy, only 200-300 of the 5,000 known mushroom species have been clearly established to be safe for consumption. Cases of mushroom poisoning have been reported with diverse clinical syndromes. A syndromic classification of mushroom poisoning has recently been developed to facilitate early interventions. We present a series of five cases of mushroom poisoning with muscarinic manifestations to highlight the difficulties we faced with exact species and toxin identification and the importance of this syndromic classification. The common symptoms in our case series are blurred vision, diarrhea, vomiting, and abdominal cramps.